Synthesis and Evaluation of Bakuchiol-Tethered Triazoles as Cytotoxic Agents - Sengar, Neha; Chatterjee, Joydeep; Kumar, Raj; Singh, Inder Pal (Synlett, 2025)
A novel series of bakuchiol-tethered triazole compounds was synthesized by reaction of azido bakuchiol with different substituted alkynes. The anticancer activity of all synthesized compounds was evaluated against A549 (lung), MCF-7, and MDA-MB-231 (breast) human tumor cells. Cytotoxicity screening showed that several compounds displayed notable cytotoxic effects against tumor cells compared to the parent molecule bakuchiol. The prominent effects were produced by compounds with IC50 values of 8.9 μM and 8.2 μM against the MCF-7 and A-549 cells, respectively.
Keywords: anticancer; bakuchiol; triazole; click chemistry; semisynthetic; cancer